On the Impact Parameter Dependence of the Ionization Energy Loss of Fast Negatively Charged Particles in an Oriented Crystal - Trofymenko, Sergii; Kyryllin, Igor; Shchus, Oleksandr (East European Journal of Physics, 2021)
When a fast charged particle passes through matter, it loses some of its energy to the excitation and ionization of atoms. This energy loss is called ionization energy loss. In rather thin layers of matter, the value of such energy loss is stochastic. It is distributed in accordance with the law, which was first received by L.D. Landau. In amorphous substances, such a distribution (or spectrum), known as the Landau distribution, has a single maximum that corresponds to the most probable value of particle energy loss. When a particle moves in crystal in a planar channeling mode, the probability of close collisions of the particle with atoms decreases (for a positive particle charge) or increases (for a negative charge), which leads to a change in the most probable energy loss compared to an amorphous target. It has recently been shown that during planar channeling of negatively charged particles in a crystal, the distribution of ionization energy loss of the particles is much wider than in the amorphous target. In this case, this distribution can be two-humped, if we neglect the incoherent scattering of charged particles on the thermal oscillations of the crystal atoms and the electronic subsystem of the crystal. This paper explains the reason for this distribution of ionization energy loss of particles. The ionization energy loss distribution of high-energy negatively charged particles which move in the planar channeling mode in a silicon crystal are studied with the use of numerical simulation. The dependence of this distribution on the impact parameter of the particles with respect to atomic planes is considered. The dependence of the most probable ionization energy loss of particles on the impact parameter is found. It is shown that, for a large group of particles, the most probable ionization energy loss during planar channeling in a crystal is lower than in an amorphous target.